Implications of Oil Inflows for Savings and Reserve Management in the Cemac. (IMF Working Papers; Working Paper ;, 2007)
This paper argues that as part of their fiscal optimization strategies CEMAC countries should be given the opportunity to invest into longer-term assets that generate market-based returns. The BEAC has created a framework of longer-term savings funds but due to low remuneration and other factors usage has remained limited. The paper also argues that regional savings in the form of reserve accumulation must be sufficient to ensure the stability of the common currency. While the current level of common foreign reserves may now be appropriate, maintaining an adequate level calls for a link between country-specific savings decisions and the setting of a regional reserve target. Strengthening and diversifying reserve management will also be desirable, a process the BEAC has embarked upon.